The evaluation of blood alcohol concentration of drivers involved in traffic accidents or suspected for alcohol in the roadside controls in four big cities of Türkiye - Can, Hale Nur; Aşırdizer, Mahmut; Bilvanisi, Sevdegül; Dursun, Recep; Duran, Latif; Karabağ, Gökmen; Arıca, Enes; Bilge, Adnan; Aydın, Faruk; Sever Tilki, Gizem Demet (The Bulletin of Legal Medicine, 2022)
Objective: Previous studies have revealed a relationship between the driving under the influence of alcohol (DUIA) and/or driving under the influence drugs (DUID) and the increased risk of death and injury in traffic accidents. The aim of this study was to investigate of blood alcohol concentration (BAC) of drivers after involved in a traffic accident or for suspected for drunkenness in the roadside traffic control in the Turkey’s four major cities. Methods: In this study, we retrospectively reviewed the laboratory registrations in university hospitals in four big cities of Turkey (Van, Manisa, Diyarbakır and Samsun) for BAC for five years (from 1 January 2015 to 31 December 2019) of the drivers. Results: In 342 cases (7.1%), BACs were above the cut-off value (0.01 g/100 mL). Of the cases sent for alcohol determination, 11.3% were women and 88.7% were men, and their mean age was 35.3±13.1. In 342 alcohol positive cases, BACs were above 0.101% in 58.8% of cases. BAC positivity of the cases was 9.4% in Manisa, 6.3% in Van, 5.3% in Samsun, and 5% in Diyarbakır. BAC was found to be positive in 4.4% (n=24) of females and 7.4% (n=318) of males (p<0.05). Conclusion: This study is one of the limited number of multicentre studies in this field; it was concluded in the study that zero tolerance should be for drunk driving in traffic, the deterrence of fines should be increased, and roadside screening tests should be used more widely.